giúp mình câu d bài 10
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 10:
\(\dfrac{a+b}{a-b}=\dfrac{c+a}{c-a}\left(a\ne b\ne c\right)\\ \Leftrightarrow\left(a+b\right)\left(c-a\right)=\left(c+a\right)\left(a-b\right)\\ \Leftrightarrow ac-a^2+bc-ab=ac-bc+a^2-ab\\ \Leftrightarrow2a^2=2bc\\ \Leftrightarrow a^2=bc\)
\(b,N=\left(2x-1\right)^2-4\ge-4\\ N_{min}=-4\Leftrightarrow x=\dfrac{1}{2}\\ c,P=\left(2x-5\right)^2+6\left(2x-5\right)+9-4\\ P=\left(2x-5+3\right)^2-4=\left(2x-2\right)^2-4\ge-4\\ P_{min}=-4\Leftrightarrow x=1\\ d,Q=\left(x^2-2x+1\right)+\left(y^2+4y+4\right)+1\\ Q=\left(x-1\right)^2+\left(y+2\right)^2+1\ge1\\ Q_{min}=1\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=-2\end{matrix}\right.\)
6a.
$M=x^2-x+1=(x^2-x+\frac{1}{4})+\frac{3}{4}$
$=(x-\frac{1}{2})^2+\frac{3}{4}\geq \frac{3}{4}$
Vậy $M_{\min}=\frac{3}{4}$ khi $x-\frac{1}{2}=0\Leftrightarrow x=\frac{1}{2}$
Bài 19:
a: \(A=5x+\dfrac{1}{9}y=5\cdot\dfrac{-1}{10}+\dfrac{1}{9}\cdot4.8=\dfrac{-1}{2}+\dfrac{8}{15}=\dfrac{-15+16}{30}=\dfrac{1}{30}\)
b: \(A=x-\dfrac{2}{3}=\dfrac{-1}{3}-\dfrac{2}{3}=-1\)
\(a,7x-2x-\dfrac{2}{3}y+\dfrac{7}{9}y=5x+\dfrac{1}{9}y\\ =5.\left(\dfrac{-1}{10}\right)+\dfrac{1}{9}.4,8\\ =\dfrac{-1}{2}+\dfrac{8}{15}=\dfrac{1}{30}\\ b,x=\dfrac{0,2-0,375+\dfrac{5}{11}}{-0,3+\dfrac{9}{16}-\dfrac{15}{22}}\\ =\dfrac{-1}{3}+\dfrac{\dfrac{-7}{40}+\dfrac{5}{11}}{\dfrac{21}{80}-\dfrac{15}{22}}\\ =\dfrac{-1}{3}+\dfrac{\dfrac{123}{440}}{\dfrac{-369}{880}}=\dfrac{-1}{3}+\dfrac{-2}{3}=\dfrac{-3}{3}=\left(-1\right)\)
Lơ giải:
\(\frac{25}{16}=(\sin a+\cos a)^2=\sin ^2a+\cos ^2a+2\sin a\cos a=1+2\sin a\cos a\)
\(\Rightarrow \sin a\cos a=\frac{9}{32}\)
\((\sin a-\cos a)^2=(\sin a+\cos a)^2-4\sin a\cos a=\frac{25}{16}-4.\frac{9}{32}=\frac{7}{16}\)
\(\Rightarrow \sin a-\cos a=\pm \frac{\sqrt{7}}{4}\)
Do đó:
\(D=\sin ^3a-\cos ^3a=(\sin a-\cos a)(\sin ^2a+\sin a\cos a+\cos ^2a)\)
\(=(\sin a-\cos a)(1+\sin a\cos a)\)
\(=\pm \frac{\sqrt{7}}{4}(1+\frac{9}{32})=\pm \frac{41\sqrt{7}}{128}\)
Lơ giải:
\(\frac{25}{16}=(\sin a+\cos a)^2=\sin ^2a+\cos ^2a+2\sin a\cos a=1+2\sin a\cos a\)
\(\Rightarrow \sin a\cos a=\frac{9}{32}\)
\((\sin a-\cos a)^2=(\sin a+\cos a)^2-4\sin a\cos a=\frac{25}{16}-4.\frac{9}{32}=\frac{7}{16}\)
\(\Rightarrow \sin a-\cos a=\pm \frac{\sqrt{7}}{4}\)
Do đó:
\(D=\sin ^3a-\cos ^3a=(\sin a-\cos a)(\sin ^2a+\sin a\cos a+\cos ^2a)\)
\(=(\sin a-\cos a)(1+\sin a\cos a)\)
\(=\pm \frac{\sqrt{7}}{4}(1+\frac{9}{32})=\pm \frac{41\sqrt{7}}{128}\)